Pengaruh Social Media Marketing dan Electronic Word of Mouth (E-WOM) Terhadap Keputusan Pembelian Tiket Eco Active Park Batu (Studi Pada Followers Tiktok @Ecoactivepark) - Ulfa Ayu Andira; Musthofa Hadi; Rena Feri Wijayanti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of social media has transformed marketing strategies in the tourism sector through the use of TikTok as a promotional platform. In addition, Electronic Word of Mouth (e-WOM) plays an important role in influencing purchase decisions by spreading information and users' experiences on social media. This study aims to analyze the partial and simultaneous influence of Social Media Marketing and Electronic Word of Mouth (e-WOM) on the purchase decision of Eco Active Park Batu tickets among followers of the TikTok account @ecoactiveparkofc. This study employed a quantitative method with a descriptive approach. A purposive sampling technique was used to select 100 respondents. Data were collected through an online questionnaire and were analyzed using multiple linear regression analysis, the t-test, the F-test, and the coefficient of determination with the assistance of SPSS software. The results showed that Social Media Marketing had a positive and significant influence on the purchase decision of Eco Active Park Batu tickets. Electronic Word of Mouth (e-WOM) also had a positive and significant influence on Purchase Decision. Furthermore, Social Media Marketing and Electronic Word of Mouth (e-WOM) simultaneously had a positive and significant influence on the purchase decision of Eco Active Park Batu tickets. Both variables explained a substantial proportion of the variation in Purchase Decision, while the remaining variation was influenced by other factors beyond the scope of this study. Based on the findings, it can be concluded that Social Media Marketing and Electronic Word of Mouth (e-WOM) have a positive and significant influence on the purchase decision of Eco Active Park Batu tickets, both partially and simultaneously. Therefore, the management of Eco Active Park Batu is encouraged to optimize its Social Media Marketing strategy by creating creative, informative, and interactive TikTok content, while strengthening positive Electronic Word of Mouth (e-WOM) by encouraging visitors to share reviews and positive experiences to increase ticket purchase decisions.